N, N'‐Diphenylthiourea electrochemical sensor for the detection of l‐glutamate and Aspartate in beef. Issue 11 (16th October 2020) - Wang, Xiaodan; Hu, Feng; Zhu, Lingtao; Liu, Dengyong; Dong, Yanli; Wang, Cuilian; Wu, Duo
Abstract : Abstract: This study was conducted to design an electrochemical sensor for detection of l ‐glutamate (L‐Glu) and Aspartate (Asp), which contribute largely to the umami taste of beef. Using N, N' ‐diphenylthiourea (DPTU), polypyrrole (PPy), and polyvinyl chloride (PVC), a composite electrode (DPTU/PVC/PPy/Pt) was prepared for rapidly electrochemical detection of l ‐Glu and Asp. The surface morphology of the synthesized functionalized electrode was characterized by Field Emission Scanning Electron Microscopy (FESEM). Potentials of umami amino acids accounted for 97.8%, while six interferential amino acids existed. The linear correlation between the content of l ‐Glu and Asp in beef broth was studied under different treatment conditions. The sensor compared with an amino acid analyzer well detected the contents of l ‐Glu and Asp in beef broths, with a coefficient of 0.991 in Pearson correlation analysis and an accuracy of 88.9%. The proposed electrochemical sensor showed good concurrence with previously reported methods and was effectively employed for the quantification of l ‐ Glu and Asp in beef. Practical Application: The sensor exhibits the good performance with high stability and high accuracy. And it is a potential sensing platform with good reproducibility, making the proposed method suitable and reliable for routine analysis of L‐Glu and Asp in beef. This method was proved promising for quantitative detecting amino acids in beef.